Improving Blood Product Transfusion Premedication Plan Documentation: A Single-institution Quality Improvement Effort. Issue 3 (14th May 2022) - Sitthi-amorn, Jitsuda; Denton, Emily; Harper, Erin; Carias, Delia; Hashmi, Saman; Bami, Sakshi; Ast, Allison; Landry, Taylor; Pettit, Kenneth L.; Gorantla, Shilpa; Vinitsky, Anna; Zheng, Yan; et al.
Abstract : Introduction: Premedication with acetaminophen and/or diphenhydramine to prevent febrile nonhemolytic transfusion reactions and minor allergic transfusion reactions is a common practice based on historical recommendations. However, recent small randomized-controlled trials showed no benefit of premedication. This inconsistency leads to practice variability, which results in the inefficiency of our institution's blood product ordering process. This project aimed to improve the number of transfusion encounters with premedication plan documentation from a baseline of 19% to 80% in 12 months. Methods: A multidisciplinary quality improvement (QI) team used QI tools to design interventions to improve the efficiency of the ordering process for blood products. Measures were tracked monthly and analyzed using statistical process control. Results: From September 2018 to January 2021, 5, 351 blood product transfusion visits were scheduled. At baseline, 34% of patients received premedication, and 19% had premedication plans documented. Interventions included a passive computerized provider order entry alert, clinical care pathway development, and clinician education. Postimplementation, the average number of encounters with a premedication plan increased from 19% to 87%, whereas encounters receiving premedication decreased from 34% to 25%. There was no change in the average number of transfusion reactions (1.8 per 100 transfusions). Conclusions: Using QI methods, our team successfully standardized the blood product premedication plan documentation despite unclear best practices regarding blood product transfusion premedication. The team added premedication plan documentation training to new employee orientation for sustainability.